Insulin-Like Growth Factor 2 mRNA-Binding Protein 3 Influences Sensitivity to Anti-IGF System Agents Through the Translational Regulation of IGF1R - Mancarella, Caterina; Pasello, Michela; Manara, Maria Cristina; Toracchio, Lisa; Sciandra, Evelina Fiorenza; Picci, Piero; Scotlandi, Katia (Frontiers in Endocrinology, 2018)
Insulin-like growth factor 2 (IGF2) mRNA-binding protein 3 (IGF2BP3) is an oncofetal protein that binds RNA, thereby influencing the fate of target transcripts. IGF2BP3 is synthesized de novo in cancer, where it promotes proliferation, drug resistance and metastasis via both IGF2-dependent and IGF2-independent mechanisms. Ewing sarcoma (ES) is a rare bone and soft tissue tumor in which the IGF system plays a pivotal role. This study aimed to investigate the effect of IGF2BP3 on the regulation of the IGF system in ES. Among the components of the IGF axis, a direct significant correlation was identified between IGF2BP3 and IGF1R at mRNA and protein levels in two independent series of clinical specimens from patients with localized ES. After the formal demonstration of a direct association between IGF2BP3 and IGF1R mRNA using ribo-immunoprecipitation assay, we performed in vitro studies using A673 and TC-71 ES cell lines to demonstrate that IGF2BP3 loss promotes the downregulation of IGF1R and a decreased biological response to IGF1, represented by reduced migration and cell growth. Additionally, the compensatory activation of insulin receptor (IR) and its mitogenic ligand IGF2, is triggered in some but not all cell lines in response to IGF2BP3-mediated IGF1R loss. These findings have therapeutic implications because cells with a decreased expression of IGF2BP3/IGF1R axis but an increased expression of the IR/IGF2 loop display higher sensitivity to the dual inhibitor OSI-906 than do control cells. Therefore, studies on IGF2BP3, which was confirmed as a post-transcriptional regulator of IGF1R, provide a step forward in the identification of new mechanisms regulating the IGF system. In addition, our results demonstrate that the detection of IGF2BP3 expression should be combined with the assessment of the IGF1R/IR ratio to predict cell responses to anti-IGF1R/IR agents.